(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Food insecurity refers to a household’s having “limited or uncertain availability of food, or limited or uncertain ability to acquire acceptable foods in socially acceptable ways”. Iron deficiency and iron deficiency anaemia, are the most prevalent nutritional deficiencies worldwide and related to household food insecurity. Objectives: To find out the association between household food security and anaemia in children of a selected rural area of Bangladesh. Materials and Methods: This descriptive cross-sectional study was conducted among children ranging age from 12 to 60 months during the period ofJanuary 2009 to June 2009in Chandpur district. Mothers of the children were the respondents. A total of 192 children selected by simple random sampling were included in the study. Data were collected by face-to-face interview of the respondents and by estimation of haemoglobin of the children. Results: The mean age of the children was 34.5 ± 16.8 months. Male children were more than the female children with male to female ratio being 3:2. The average monthly family income was taka 7500. More than 60% of the mother had secondary level education. Farming was the prime occupation (36.4 %) of the father followed by business (25.5%) and service (22.4%). About 36% of the household did not have food security and nearly 45% of the children wereanaemic (Hb<11 g/dl). About two-thirds (65.2%) children with household food insecurity was anaemic (Hb 11g/dl). Estimation of odds ratio demonstrates that food insecured children were nearly 3 times as likely to develop anaemia as the children having household food security. The present study revealed a significant association (P<0.001) between household food security and anaemia in children. Household food security was not influenced by age and gender of the children. Low family income and mother’ illiteracy was significantly associated with household food insecurity. Conclusion: The present study revealed a significant association between household food insecurity and anaemia in children. Household food security was not influenced by age and gender of the children. However, low family income and mothers’ illiteracy play significant role in household food security. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 130-133